GEOCHEMISTRY OF LATE MESOZOIC ADAKITES FROM THE SULU BELT, EASTERN CHINA: MAGMA GENESIS AND IMPLICATIONS FOR CRUSTAL RECYCLING BENEATH CONTINENTAL COLLISIONAL OROGENS - Guo F.; Fan W.; Li Ch. (My University, 2006)
Both low-Al and high-Al adakitic andesites erupted at ~ 114 Ma in the Sulu collisional belt, eastern China, provide evidence for recycling of continental crust into the mantle more than 100 million years after the Triassic (~ 240 Ma) collision between the North China and Yangtze blocks. These rocks display similar normalized trace element patterns, with enrichments in large ion lithophile elements (LILE), light rare earth elements (LREE) and depletions in Nb, Ta and Ti, and have highly radiogenic Sr and non-radiogenic Nd isotopic compositions (high-Al: 87Sr/86Sr(i)=0.70645-0.70715 and εNd(t)=-20.1 to -19.1; low-Al: 87Sr/86Sr(i)=0.70593-0.70598 and εNd(t)=-17.1 to -15.8). The high-Al (Al2O3 > 15 %) adakitic andesites are compositionally comparable with experimental slab melts, whereas the low-Al series (Al2O3 ~ 13 %) have higher MgO, Cr and Ni, and higher Sr/Y ratios, and are compositionally comparable with slab melts hybridized by mantle peridotites. Combined major- and trace-element and Sr-Nd isotope data indicate that the two types of adakitic andesites have been derived from a LILE- and LREE-enriched eclogitic lower continental crust; in the case of the high-Al adakitic andesites, the melts underwent insignificant mantle contamination, whereas the low-Al magmas reacted with peridotites. Generation of the two types of late Mesozoic adakitic andesites favours a model of lithospheric delamination, leading to asthenospheric upwelling and extensive melting of lower continental crust, including a delaminated block, in the Sulu belt.
Keywords: GEOCHEMISTRY; LOWER CONTINENTAL CRUST; ADAKITES; LATE MESOZOIC; SULU BELT; Мезозой::Триасовая; Mesozoic::Triassic